Organomodified Silicone Elastomer (OMSE) for Next Generation Personal Care Products - Vaidya, Ashish Anant; Balu, K.; Chavan, Mohan Vijaykumar; Ghosh, Nilmoni; Kumar, Amit (Journal of Research Updates in Polymer Science, 2013)
Personal care (PC) products containing commercial silicone elastomer (SE) blends offer superior sensory, due to their silky and non-greasy characteristics. These products contain functional organic actives; namely sunscreens, antibacterial agents and dyes. The functional performance of the PC products is determined by the extent of deposition of the actives on the skin or hair. However, this performance is limited due to incompatibility of organic actives with the silicone elastomer (SE) blend. This review described recent development of organomodified silicone elastomers (OMSE) for enhanced compatibility and superior deposition of actives on the skin or hair. OMSEs contain covalently linked functional actives to the cross-polymeric silicone backbone. OMSE were synthesized by reacting alkenyl functional derivatives of avobenzone, benzylidene malonate, curcumin or hydroxyanthraquinone, suitable crosslinker, solubilizing (e.g. CnH2n i.e. alkyl) / emulsifying agents (e.g. polyether) with the poly(dimethyl)-co-(methylhydrogen)siloxane copolymer in the presence of platinum catalyst. OMSE showed superior functional performance due to uniform molecular distribution of sunscreen / dye molecules on the substrate surface. Covalently attached sunscreen / dye molecules on the cross-polymeric silicone backbone would show enhanced safety profile due to negligible possibility of penetration through skin.